Spontaneous Dissections of Bilateral Internal Carotid and Vertebral Arteries due to Intractable Vomiting - Gift Echefu; Rameela Mahat; Raju Vatsavai; Steven Zuckerman (Case Reports in Vascular Medicine)
In young adults, spontaneous craniocervical arterial dissections (sCAD), which involve the major arteries of the head and neck, are associated with an increased risk of stroke. sCAD occurs in the absence of major trauma as seen in traumatic craniocervical artery dissection. It may affect unilateral or bilateral carotid or vertebral arteries. Cases of spontaneous bilateral carotid and vertebral artery dissections occurring simultaneously are extremely rare. We present a case of a 49-year-old female with no history of arteriopathy who presented with aphasia and right upper extremity weakness and was found to have dissections in bilateral extracranial and intracranial carotid arteries, as well as the bilateral vertebral arteries. She had symptomatic improvement with antithrombotic therapy and aggressive outpatient rehabilitation.